THREE LEVELS OF NATURE IN THE EMBODIMENT OF JAWI TEMPLE - Andini, Ni Putu Ayu Mesa; Paramadhyaksa, I Nyoman Widya; Titisari, Ema Yunita; Suryada, I Gusti Agung Bagus (Border: Jurnal Arsitektur, 2025)
Jawi Temple as a relic of the Singasari Kingdom is vertically composed of three levels of buildings, namely the base, body, and roof which are terraced, tall and slender, and towering, resulting in the idea to conduct a study related to the symbolic meaning in the form of the three segments. This article is a summary of the results of qualitative research on the interpretation of the symbolic meaning of the three segments of the Jawi Temple building. The results of the study obtained show that (a) the three levels of the Jawi Temple building are interpreted as the feet, body, and top of the mountain; (b) the three levels of the Jawi Temple building are interpreted as the feet, body, and head of humans; (c) Jawi Temple contains symbolic meaning as the natural levels of Bhūrloka, Bhuvarloka, and Svarloka in Hinduism and the natural levels of Kamaloka, Rupaloka, and Arupaloka in Buddhism; (d) Jawi Temple is a symbolization of Mount Meru which has a foot, body, and peak which in its top area is the location of the Kingdom of Heaven; and (e) the four similar faces of Jawi Temple are symbolic of Cosmogony in Hinduism and the embodiment of Lord Brahmā.